NAVOI AND TURKISH CRITICISM - Abdumalik Kurbonov (Scholar Express Journal, 2022)
In the article, the author provides information about Navoi's work, in particular, works of this genre created in Turkey under the influence of his tazkira. He tries to scientifically substantiate their significance by analyzing the tazkirs created in Turkey
Keywords: Tazkira, Ashiq Chalabi; Mashoir ush-shuaro; tatabbu; Mustafa Eson